Genetic relatedness study of jatropha curcas genotypes using rapd molecular markers - Nur Syuhadah, Mohd Gusti (Universiti Malaysia Sarawak, UNIMAS, 2013)
Jatropha curcas is widely known as a source of high quality biodiesel. Due to the high demand of research on J. curcas accession, study of genetic relatedness of J. curcas accession from Sarawak (Lundu) to the other widely research J. curcas accession (Africa, Thailand and Indonesia) were conducted. The aim of this study was to assess the genetic relatedness of four different breeds of J. curcas (Africa, Thailand, Lundu (Sarawak, Malaysia) and Indonesia) by using RAPD marker. 10-mers primers were used to assess the genetic relatedness among the breeds. Jaccard formulation was used to calculate the similarity matrix. The RAPD-PCR analysis obtained shows high similarity matrix between Thailand and Indonesia (0.67) showing that both breeds come from a narrow genetic ancestor. Low similarity matrix of J. curcas of breed from Africa and Lundu to the other accession suggests that the breeds were not closely related. The successful revelation of genetic relatedness among the breeds indicates the effectiveness of RAPD profiling in the study. The outcomes of the study and the breeds are a good source for the development of excellent c J. curcas cultivars.